Hypertonic Saline Solution Reduces Microcirculatory Dysfunction and Inflammation in a Rat Model of Brain Death. Issue 4 (April 2019) - Correia, Cristiano de Jesus; Armstrong, Roberto; Carvalho, Priscila Oliveira de; Simas, Rafael; Sanchez, Daniela Crisina Janolli; Breithaupt-Faloppa, Ana Cristina; Sannomiya, Paulina; Moreira, Luiz Felipe Pinho
ABSTRACT: Background: Brain death (BD) induces hemodynamic instability with microcirculatory hypoperfusion, leading to increased organ inflammation and dysfunction. This study investigated the effects of 7.5% hypertonic saline solution (HSS) on mesenteric microcirculatory dysfunction and inflammation in a rat model of BD. Methods: Male Wistar rats were anesthetized and mechanically ventilated. BD was induced by rapidly inflating an intracranial balloon catheter. The rats were randomly divided into: SH, sham-operated rats subjected to trepanation; NS, rats treated with NaCl 0.9%, 4 mL/kg immediately after BD; T1, rats treated with HSS (NaCl 7.5%, 4 mL/kg) immediately or 60 min after BD, T60 . All groups were analyzed 180 min after the start of the experiment. Results: Rats in BD groups presented with a similar hypertensive peak, followed by hypotension. Proportion of perfused small vessels was decreased in the NS group (46%) compared with the SH group (74%, P = 0.0039). HSS restored the proportion of perfused vessels (T1 = 71%, P = 0.0018). The anti-endothelial nitric oxide synthase (eNOS) protein expression significantly increased in rats given HSS (T1, and T60, P = 0.0002). Similar results were observed regarding endothelin-1 ( P < 0.0001). Increased numbers of rolling ( P = 0.0015) and migrated ( P = 0.0063) leukocytes were observed in the NS group compared with the SH group. Rats given HSS demonstrated an overall reduction in leukocyte–endothelial interactions. The ICAM-1 levels increased in the NS group compared with the SH group, and decreased in the HSS-treated groups ( P = 0.0002). Conclusions: HSS may improve the density of mesenteric perfused small vessels due to its effects on eNOS and endothelin-1 protein expression, and reduces inflammation by decreasing leukocyte adhesion and migration in a rat model of BD.